Comparison of 2 Equine Transfixation Pin Casts and the Effects of Pin Removal. Issue 4 (7th April 2014) - Williams, Jarred M.; Elce, Yvonne A.; Litsky, Alan S.
<x xml:space="preserve">Abstract</x> Objective To (1) compare strain on the dorsal aspect of the proximal phalanx (P1) between 2 types of transfixation pin casts (TPC) and (2) evaluate the change in strain as the pins are removed. Study Design Experimental. Animals Equine cadaver forelimbs (n = 10 pair). Methods Each limb of a pair was assigned to 1 of 2 TPC constructs. Construct 1 consisted of a TPC with 2 positive profile, centrally threaded pins placed in the distal aspect of the third metacarpus (MC3) and construct 2 had 4 smooth Steinmann pins placed similarly. A strain gauge was mounted on P1 and axial compression (444.8–5337.9 N) applied. One forelimb of each pair was tested as a control with no construct in place. The 2 TPC groups were retested after removal of 1 proximal (n = 5 limbs) or distal (n = 5) pin from construct 1, and 2 proximal (n = 5) or distal (n = 5) pins from construct 2. Limb specimens were retested after all pins had been removed. Results There was a significant decrease in strain between both TPC constructs and the non‐casted control at all loads except 444.8 N. There was no significant difference in strain reduction between the 2 TPC constructs. After proximal pin removal there was a 7% (construct 1) and 10% (construct 2) increase in strain. When distal pins were removed there was a 0.5% (construct 1) and 1% (construct 2) increase in strain. The difference between proximal and distal pin removal was only statistically different from each other at high loads. Conclusion Both constructs provided equivalent reduction in strain. Removal of the proximal pin(s) increased the strain.